2022
DOI: 10.1007/s10055-022-00638-2
|View full text |Cite
|
Sign up to set email alerts
|

A review of cybersickness in head-mounted displays: raising attention to individual susceptibility

Abstract: Cybersickness still poses a significant challenge to the widespread usage of virtual reality, leading to different levels of discomfort and potentially breaking the immersive experience. Researchers have attempted to discover the possible fundamental causes of cybersickness for years. Despite the longstanding interest in the research field, inconsistent results have been drawn on the contributing factors and solutions to combating cybersickness. Moreover, little attention has been paid to individual susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 223 publications
0
84
0
Order By: Relevance
“…Additionally, previous research has investigated how neurotypical users could mitigate motion sickness in VR, such as through the physical hand-eye-coordination tasks, real-world natural decay and adding visual effects or elements (Dennison and Krum, 2019;Jasper et al, 2020;Tian et al, 2022). However, no study tested the efficacy of these techniques for neurodivergent users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous research has investigated how neurotypical users could mitigate motion sickness in VR, such as through the physical hand-eye-coordination tasks, real-world natural decay and adding visual effects or elements (Dennison and Krum, 2019;Jasper et al, 2020;Tian et al, 2022). However, no study tested the efficacy of these techniques for neurodivergent users.…”
Section: Discussionmentioning
confidence: 99%
“…However, as highlighted in the study by Das et al (2021), compound effects on neurodivergent users are likely to be different from the ones experienced by neurotypical users due to increased sensitivity to inducing factors. Additionally, previous research has investigated how neurotypical users could mitigate motion sickness in VR, such as through the physical hand-eye-coordination tasks, real-world natural decay and adding visual effects or elements (Dennison and Krum, 2019;Jasper et al, 2020;Tian et al, 2022). However, no study tested the efficacy of these techniques for neurodivergent users.…”
Section: Discussionmentioning
confidence: 99%
“…For the SVV, gender differences have been previously reported in which females are more likely to be influenced by the orientation of a visual background when upright [Barnett-Cowan et al, 2010] and mixed results have been found with expert observers, where dancers were found to be more susceptible to the vestibular noise generated by head tilts (Beck et al, 2020) and astronauts performed no different than a control group on earth (Harris et al, 2017). Recent reviews have also highlighted various factors related to individual, hardware, content, and experimental paradigm differences leading to the vast differences observed for susceptibility to cybersickness in the literature (Howard and Van Zandt, 2021; Tian et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time edits introduce opportunities for customized optimizations. For instance, adaptively supporting accommodation of people susceptible to cybersickness [45], [46], or prone to diverge from a pre-designed storyline (individuals with low reaction time [47]). Furthermore, they also enable system optimizations, e.g., expanding the efficacy of streaming applications.…”
Section: B Alignment Edit Strategiesmentioning
confidence: 99%
“…It is known that the interaction between visual and vestibular systems triggers self-motion, for example, in flying scenes or when a virtual object crosses the viewport [56]. [46] extensively investigated visually induced motion sickness. [57] measured just noticeable differences in the head lateral shifts, showing that it is possible to implement real-time optimizations based on content parameters, specifically object distances, that would lead to an imperceptible translation gain.…”
Section: Alignment Edit Challengesmentioning
confidence: 99%